DEMAND FOR FOOD COMMODITIES IN TULUNGAGUNG REGENCY - Nuraini Afiifah Habiibaturrohmah; Ratya Anindita; Condro Puspo Nugroho (Socio-Economics/Agribusiness Department, 2020)
Food is a basic need that must be fulfilled by every citizen / community and is the right of every resident to fulfill his food needs. So it is natural that many countries whose governments give considerable attention to food-related problems both in terms of demand and supply. Research on demand for food commodities in Tulungagung Regency uses data from SUSENAS (National Socio-Economic Survey) in 2018 obtained from the Indonesian Central Bureau of Statistics. The model used in this study is the AIDS (Almost Ideal Demand System) model with the SUR (Seemingly Unrelated Regression) method. The results showed that the factors that influenced the demand for food commodities were rice prices, corn prices, soybean prices, mungbean prices, peanut prices for cassava prices, sweet potato prices, and total household expenditure. Price elasticity is elastic for food commodities (rice, corn, green beans, peanuts, cassava and sweet potatoes). Cross elasticity has a substitution relationship in each commodity and is also complementary in each commodity. Expenditure elasticity shows that all food commodities are normal goods.